Dielectric and ferroelectric properties of 1-3 barium titanate-Portland cement composites - R. Rianyoi (2018)
In the current work, the dielectric and ferroelectric properties of 1-3 barium titanate (BT)-Portland cement (PC) composites have been studied as potential lead-free piezoelectric-cement-based composites. The 1-3 BT-PC composites were fabricated by a dice-and-fill technique with BT:PC ratios of 50:50, 60:40 and 70:30 by volume. The results indicate that the dielectric constant (εr) of the composite materials increases as the barium titanate volume fraction increases; this follows the parallel model. The room temperature εrat 1 kHz of 70% barium titanate composite was found to have values higher than 750. The loss tangent (tanδ) results were found to decrease with increasing barium titanate volume fraction. On the other hand, the ferroelectric hysteresis loops of composite materials indicate that the "instantaneous" remnant polarization (Pir) increases as the barium titanate volume fraction increases. The Pirat 15 kV/cm (90 Hz) of 70% barium titanate composite was found to have a value of ≈3 μC/cm2. © 2011 Elsevier B.V. All rights reserved.